2005
DOI: 10.1080/10428190400018364
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus 8-negative malignant effusion lymphoma: A distinct clinical entity and successful treatment with rituximab

Abstract: We describe 2 elderly patients with Human herpesvirus 8 (HHV-8)/Kaposi sarcoma herpes virus negative malignant effusion lymphoma showing pan-B-cell immunophenotyping markers and successfully treated with a chimeric anti-CD20 IgG1 monoclonal antibody, rituximab. A 90-year-old man and an 87-year-old woman were hospitalized because of pleural effusions. They were diagnosed as having malignant effusion lymphoma on the basis of cytologic and flow cytometric findings of effusions, revealing involvement of atypical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Two hundred and twelve cases in 99 papers [1,2,3,4,5,6,7,8,9,10,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,9...…”
Section: Resultsmentioning
confidence: 99%
“…Two hundred and twelve cases in 99 papers [1,2,3,4,5,6,7,8,9,10,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,9...…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, neoplastic cells display morphological, immunophenotypic and genotypic features related to DLBCL (Matsumoto et al, 2005).…”
Section: Secondarymentioning
confidence: 99%
“…41,[43][44][45][46][47] Many of these cases are KSHV-unrelated large B-cell lymphomas, also termed KSHV-unrelated PEL-like lymphomas. 45 KSHV-unrelated PEL-like lymphoma cases are associated with hepatitis C virus (HCV) (30%-40%).…”
Section: Ebv-associated B-cell Lymphoproliferative Disorders Kshv/hhvmentioning
confidence: 99%
“…All published data showed that despite the use of standard chemotherapy regimens (CHOP or CHOP-like) the prognosis is poor in comparison with that of other HIV-NHL subtypes. 6,46,152 Considering the aggressiveness of PEL and its pathogenesis, several nonchemotherapy approaches have been tested, including HAART alone or antiviral treatment (ie, cidofovir, AZT, IFN) with promising results. [153][154][155] Similarly to PEL, the prognosis of PBLs of the oral cavity type remains poor despite the use of HAART and chemotherapy.…”
Section: Treatment Of Unusual Entitiesmentioning
confidence: 99%